Expert knowledge elicitation with SHELF: one distribution, one expert - O'Hagan, Anthony (Henry Stewart Talks, 2023)
Fundamentals of elicitation, Challenges for subjective probability judgments, Sources of bias, Anchoring, availability, and overconfidence, SHELF (Sheffield Elicitation Framework) principles, Basic SHELF tertile method, SHELF 4, SHELF templates, SHELF slide sets